2002
DOI: 10.1177/009127002401102795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meloxicam on Platelet Function in Healthy Adults: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit cyclooxygenase-1 (COX-1), thereby inhibiting platelet function via blockade of thromboxane A2 (TxA2) formation, and COX-2, the enzyme that mediates inflammatory responses. Meloxicam is a relatively COX-2-selective anti-arthritis drug that shows significant TxA2 inhibition, albeit less than traditional NSAIDs. A randomized, double-blind, placebo-controlled trial was conducted in 79 healthy adults to compare the effects of once-daily therapeutic (7.5 mg, 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
39
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 12 publications
7
39
0
Order By: Relevance
“…The measurement of serum TXB 2 production by platelets following blood coagulation is a specific and most frequently used test for evaluation of platelet COX-1 activity in humans and other species (Brideau et al 1996;Blain et al 2002;Gilmer et al 2003;Jones et al 2002;Patrignani et al 1997;Rinder et al 2002;Sessions et al 2005;Van Kraaij et al 2002). Whole blood TXB 2 production is measured from clotted blood samples obtained from the patient after administration of NSAID or after collection of blood into tubes preloaded with NSAID.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of serum TXB 2 production by platelets following blood coagulation is a specific and most frequently used test for evaluation of platelet COX-1 activity in humans and other species (Brideau et al 1996;Blain et al 2002;Gilmer et al 2003;Jones et al 2002;Patrignani et al 1997;Rinder et al 2002;Sessions et al 2005;Van Kraaij et al 2002). Whole blood TXB 2 production is measured from clotted blood samples obtained from the patient after administration of NSAID or after collection of blood into tubes preloaded with NSAID.…”
mentioning
confidence: 99%
“…While searching for the literature on normal values of TXB 2 in canine serum and the measurement of serum TXB 2 after NSAID administration, we found inconsistency in the published data, which might influence the results obtained. In some studies (Blain et al 2002;Gilmer et al 2002;Jones et al 2002;McKellar et al 1990;Rinder et al 2002;Streppa et al 2002) blood samples for serum TXB 2 determination were incubated during blood clotting at 37 C for one hour as recommended (Brideau et al 1996;Patrignani et al 1997), whereas other studies (Frelinger et al 2006;Hashimoto et al 2002;Morchon et al 2006;Sunose et el. 2001a;Sunose et al 2001b;Tanus-Santos et al 2000) did not mention the incubation of samples.…”
mentioning
confidence: 99%
“…teers and nonsurgical patients have indicated that COX-2 inhibitors have virtually no effect on the gastric mucosa or platelet function. [1][2][3][4] Safety in the perioperative setting has been suggested by the lack of increased intraoperative blood loss in patients receiving this class of drug. 5,6 Despite these favourable findings, many clinicians remain hesitant to administer COX-2 inhibitors perioperatively until there is more definitive evidence that these drugs do not alter platelet function during anesthesia and surgery.…”
mentioning
confidence: 99%
“…5,6 Despite these favourable findings, many clinicians remain hesitant to administer COX-2 inhibitors perioperatively until there is more definitive evidence that these drugs do not alter platelet function during anesthesia and surgery. Such evidence may be provided by measuring platelet aggregation 2,7,8 in response to an aggregatory stimulus such as arachidonic acid (AA) or adenosine diphosphate (ADP). Whereas a myriad of potentially offsetting perioperative factors -many of which are not directly related to platelet functionmay affect measurements of blood loss, aggregometry is more sensitive to and more specific for the potential platelet inhibitory effects of a study drug.…”
mentioning
confidence: 99%
“…Meloxicam has a long track record of safety and a favorable side-effect profile compared to other dual COX inhibitors. Trials in healthy volunteers showed that meloxicam did not prolong bleeding time or affect platelet aggregation [11]. With regard to the potential gastrointestinal side effects of NSAIDs, meloxicam is very well tolerated [12].…”
mentioning
confidence: 99%